Expressive and Structural Ornamentation in Handel’s Vocal Music: A Literature and Score-Based Study - Chenchen, Xiong; Hin, Yap Jin (Grenek: Jurnal Seni Musik, 2025)
This study investigates the stylistic features and functions of ornamentation in Handel’s vocal arias, addressing the challenge posed by the absence of detailed notations in his works. The research focuses on the dual role of ornamentation as both decorative and structural, aiming to bridge historical scholarship with modern performance practices. The methodology involves a comprehensive literature study of historical treatises, including works by Tosi, Agricola, and Quantz, alongside a score-based analysis of selected Handel arias to identify and interpret ornamentation practices. Findings highlight the expressive and structural functions of ornaments, such as enhancing melodic connectivity, harmonic depth, and emotional expression. The study emphasizes the performer’s discretion in applying ornaments, particularly in improvisatory contexts like da capo arias. This research contributes to understanding Handel’s compositional intentions and offers valuable insights for historically informed performance (HIP). Future studies could explore cross-genre ornamentation, technological applications, and evolving audience perceptions of Baroque vocal embellishments